Developing a people capability framework to promote sustainability in facility management practices - Sarpin, Norliana (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to introduce a research study that aims to establish a people capability framework to promote the sustainability agenda in facilities management (FM) practices. Design/methodology/approach – Through a literature review, a range of factors relating to people capabilities in the context of sustainability endeavours is identified. Aquestionnaire survey of industry practitioners and statistical data analysis help prioritise these people capability factors and evaluate the role played by each factor in promoting sustainability in FM practices. Findings – Twenty-three people capability factors are identified as significant to the promotion of sustainability measures in FM practices. Dealing with these factors effectively can provide a sound basis for equipping FM professionals with the necessary knowledge, information on training and educational needs and the right mindset to enhance the implementation of sustainability in FM practices. Practical implications – The research shows the importance of capabilities and skills in the pursuit of sustainability in professional practice. In addition, it highlights specific areas for improvement in the FM sector. Originality/value – The research links the importance of sustainability with the mindset and preparedness of FM practitioners. It emphasises people capabilities, in addition to technological advancement and financial implications, in the promotion of sustainability in the building industry.